Comparison of the binding of the gastrin-releasing peptide receptor (GRP-R) antagonist 68Ga-RM2 and 18F-FDG in breast cancer samples - Morgat, Clément; Schollhammer, Romain; Macgrogan, Gaétan; Barthe, Nicole; Vélasco, Valérie; Vimont, Delphine; Cazeau, Anne-Laure; Fernandez, Philippe; Hindié, Elif (PloS one, 2019)
The Gastrin-Releasing Peptide Receptor (GRPR) is over-expressed in estrogen receptor (ER) positive breast tumors and related metastatic lymph nodes offering the opportunity of imaging and therapy of luminal tumors. 68Ga-RM2 binding and 18F-FDG binding in tumoral zones were measured and compared using tissue micro-imaging with a beta imager on 14 breast cancer samples (10 primaries and 4 associated metastatic lymph nodes). Results were then assessed against ER expression, progesterone receptor (PR) expression, HER2 over-expression or not and Ki-67 expression. GRPR immunohistochemistry (IHC) was also performed on all samples. We also retrospectively compared 68Ga-RM2 and 18F-FDG bindings to 18F-FDG SUVmax on the pre-therapeutic PET/CT examination, if available. 68Ga-RM2 binding was significantly higher in tumors expressing GRPR on IHC than in GRPR-negative tumors (P = 0.022). In ER+ tumors, binding of 68Ga-RM2 was significantly higher than 18F-FDG (P = 0.015). In tumors with low Ki-67, 68Ga-RM2 binding was also significantly increased compared to 18F-FDG (P = 0.029). Overall, the binding of 68Ga-RM2 and 18F-FDG displayed an opposite pattern in tumor samples and 68Ga-RM2 binding was significantly higher in tumors that had low 18F-FDG binding (P = 0.021). This inverse correlation was also documented in the few patients in whom a 18F-FDG PET/CT examination before surgery was available. Findings from this in vitro study suggest that GRPR targeting can be an alternative to 18F-FDG imaging in ER+ breast tumors. Moreover, because GRPR antagonists can also be labeled with lutetium-177 this opens new avenues for targeted radionuclide therapy in the subset of patients with progressive metastatic disease following conventional treatments.